The Problem of Ineffability in Dewey's Theory of Inquiry. - Gale, Richard M. (Southern Journal of Philosophy)
A Deweyan inquiry begins with an indeterminate situation and terminates, when successful, with a determinate situation, both of which Dewey holds to be unique and therefore ineffable. This ineffability requirement has the disastrous consequences that Dewey's beloved collective inquiry is impossible and that there are no objective criteria for the success of inquiry. It is found that Dewey's ineffability requirement results from his misbegotten attempt to aestheticize inquiry so that it is an act of artistic creation. It is suggested that things would go better if he dropped the ineffability requirement.